Informality and multidimensional child poverty: evidence from urban and rural Indonesia - M. Afif Khoiruddin; Agus Suman; Ferry Prasetyia; Susilo; Erlyn Yuniashri (Development Studies Research)
Despite growing attention to child poverty in developing countries, limited empirical evidence exists on how household labor informality contributes to multidimensional child poverty in Indonesia. This study addresses this gap by examining the relationship between employment status and child deprivation using nationally representative data from the 2022 Indonesian National Socioeconomic Survey (Susenas). Multidimensional child poverty is measured through seven deprivation indicators following the Multiple Overlapping Deprivation Analysis framework. Using binary and multinomial logit regressions, we estimate the effects of formal, informal, and self-employment (in both agricultural and non-agricultural sectors) on children’s poverty status across national, rural, and urban contexts. Our findings reveal that informal employment is consistently associated with higher risks of multidimensional child poverty, particularly in rural areas. In contrast, formal employment and non-agricultural self-employment reduce poverty risks. Socio-demographic characteristics such as parental education, number of children, and single-parent status also play a critical role in shaping child deprivation. Access to social protection significantly mitigates poverty risks. The results highlight two critical policy insights: the need to facilitate transitions from informal to formal employment especially in rural areas, and the importance of integrating inclusive social protection programs that target vulnerable households to break intergenerational cycles of poverty.